The Relationship between School Climate and Teacher Self-Efficacy in PAUD Ummul Habibah Kelambir V Medan Village - Parapat, Asmidar; Lubis, Sofni Indah Arifa; Tumiran, Tumiran (International Conference on Sciences Development and Technology, 2023)
This research aims to find out whether there is a relationship between school climate and teacher self-efficacy , how much contribution is made, and whether this is significant or not. This research was carried out in March 2022 – June 2022 among PAUD Ummul Habibah Medan teachers. The research method used is a quantitative method. The sampling technique is that the population is the same as the sample, meaning 100% of the population. The research instrument used was a questionnaire in the form of multiple choices. Meanwhile, the correlation technique used is product moment. The results found in this research were that there was a significant relationship between school climate and job satisfaction of Ummul Habibah PAUD teachers, Kelambir V Village, Medan. The results of this research show that the calculated r is 0.563 and is in the quite strong category (the calculated r value is in the range of 0.40-0.699) with a KD value of 31%. Thus, there is a fairly strong and significant relationship between school climate and the self - efficacy of Ummul Habibah PAUD teachers, Kelambir V Village, Medan, and the school climate makes a strong contribution in increasing the self-efficacy of Ummul Habibah PAUD teachers, Kelambir V Medan Village.at the end of the PKM series. This allowed the team to determine how well the participants understood the material.